The Influence of Perception of Benefits and Sharia Principles on the Intention to Use QRIS Sharia in Halal MSMEs - Riyan Pradesyah; Fahriani Astuti Sitepu; Abdul Hadi Ismail (Universitas KH. Abdul Chalim Mojokerto, 2026)
The development of digital payment technology has encouraged the presence of QRIS Syariah as a payment system that not only offers easy transactions but also ensures compliance with sharia principles. This study aims to analyze the influence of Perceived Benefits and Sharia Principles on the Intention to Use QRIS Syariah in halal MSMEs. This study used a quantitative approach by distributing a questionnaire containing 30 statements to 35 halal MSME respondents. The data obtained were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method through the SmartPLS application. The results of the outer model test showed that all indicators in the three variables had outer loading values ​​above 0.70 so that the instrument was declared valid and reliable. The R-Square value of 0.648 indicates that Perceived Benefits and Sharia Principles are able to explain 64.8% of the variation in Intention to Use QRIS Syariah. In hypothesis testing, Perceived Benefits have a positive but insignificant influence on usage intention, indicated by a t-statistic value of 1.282. Conversely, Sharia Principles have a positive and significant influence with a t-statistic of 2.604, making it the most dominant factor in driving the intention to use Sharia QRIS. This finding indicates that for halal MSMEs, Sharia compliance is a primary consideration in adopting Sharia digital payment services, while technical benefits are not yet a fully determining factor. This study implies that the development and socialization strategy for Sharia QRIS needs to emphasize Sharia values ​​to increase user interest among halal MSMEs.